The Prevalence of Cleft Lip and Palate Patients: A Single-Center Experience for 17 Years - (:unkn) unknown (AVES, 2019)
Objective: The aim of the present study was to report the prevalence of cleft lip and palate (CLP), isolated cleft palate (CP), isolated cleft lip (CL), and median cleft (MC) applied in Marmara University School of Dentistry, Department of Orthodontics. Methods: There were 1058 patients who applied to the center between 2000 and 2017. A total of 1026 patients were included in the study. Files, models, and photographs were evaluated.The patients were divided into six groups: unilateral right or left CLP, bilateral CLP, isolated CP, isolated CL, and MC. The prevalence was identified according to cleft type, side, gender, age, and application year. Results: The most common type was unilateral CLP (44.3%), which was observed more on the left side (28.9%), followed by CP (28.7%). MC had a minimum ratio (0.3%) between cleft types. Males were more prone to have unilateral CLP (right side, 64.6%) and bilateral CLP (64.1%), whereas females were more prone to have CP (59.9%). The greatest number of applications was recorded in 2004, and the patients mostly applied in the neonatal period (64.9%). The ratios of complete cleft cases in all types of clefts were statistically significantly higher. Conclusion: Unilateral CLP was the most common cleft type and seen more on the left side. While males were affected more by CLP, isolated CP was seen more in females than in males.
Keywords: Cleft lip and palate; prevalence; single center; CONGENITAL-ANOMALIES; ORAL CLEFTS; EPIDEMIOLOGY